Mesozeaxanthin protects the liver and reduces cardio-metabolic risk factors in an insulin resistant rodent model - Şahin, Kazım; Orhan, Cemal; Akdemir, Fatih; Tuzcu, Mehmet; Şahin, Nurhan; Yilmaz, Ismet; Juturu, Vijaya (Taylor & Francis Ltd, 2017)
Background: Mesozeaxanthin (MZ) is a macular carotenoid which has been reported to have a number of pharmacological properties, including the antioxidant, and anticarcinogenic property, and has been stated to decrease the hepatocyte lipid content. Objective: In this study, we investigated the effect of MZ on cardio-metabolic health risk (CMHR) and its probable mechanisms of action in rats fed a high-fat diet (HFD). Design: Rats were randomly divided into four groups consisting of (i) Control, (ii) MZ, (iii) HFD, and (iv) HFD+MZ. Results: MZ treatment increased the antioxidant enzyme activities and helped improve the liver function. The treatment alleviated CMHR and decreased the level of nuclear factor kappa B (NF-kappa B p65) and tumor necrosis factor-alpha (TNF-alpha). The levels of hepatic peroxisome proliferator-activated receptor gamma (PPAR-gamma), phosphorylated insulin receptor substrate 1 (p-IRS-1), beta,beta-carotene 9', 10'-oxygenase 2 (BCO2) and nuclear factor erythroid 2-related factor 2 (Nrf2), which decrease in HFD rats, were found to be significantly higher in MZ supplemented animals. Conclusion: MZ has antioxidant and anti-inflammatory properties and can is reported in this study toprotect against fatty liver and cardio-metabolic syndrome, possibly through regulation of PPAR-gamma, IRS-1, Nrf2 and NF-kappa B proteins, in an insulin-resistant rodent model.
Keywords: High-fat diet; insulin resistance; liver; mesozeaxanthin; rats